Mereduksi Konflik Dalam Organisasi (Fenomena Konflik Di Lembaga Pendidikan Yayasan - Sri Lestari, Ambar (Proceedings of Annual Conference on Islamic Educational Management, 2021)
Abstract: This study aims to provide an overview of conflicts that occur in organizations, especially in an educational institution under the Foundation. The significance of this research is on conflict management in organizations that need to be understood by school members because conflict has broad implications if it cannot be managed properly. Through a case study approach, participants at the Foundation’s educational institutions were willing to be interviewed, including leaders, teachers and representatives of parents. Data collection through semi-structured interviews was conducted to obtain participant views on the conflict theme in the organization. The findings show that in educational institutions at the Foundation, there are several things that cause conflict within the organization, including: communication between leaders and staff, teachers and even parents of students which often does not occur in synchronization, conflict management is still low and dominated by foundations, lack of listening to the aspirations of staff, teachers even parents. The implication of this research is the lack of leadership sensitivity can have a psychological impact on the continuity of the organization which results in the health of individuals in working mentally and physically.